On limitations of solutions of a linear uniform second-order equation in Gilbert space - Mamij, K. S. (Lithuanian Mathematical Journal, 1965)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:К. С. Мамий, Об ограниченности решений линейною однородного уравнения второго порядка в гильбертовом пространствеK. S. Mamij, Apie Hilberto erdvėje tiesinės antros eilės homogeninės lygties sprendinių aprėžtumą